ผลของการเผาไหม้แบบเติมอากาศเป็นขั้นต่อการปล่อยไนโตรเจนออกไซด์จากการเผาไหม้ร่วมของถ่านหินและชีวมวลในฟลูอิไดซ์เบดแบบหมุนเวียน - ชาญวิทย์ กมลรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This research studied the effects of air staged combustion on NOx emissions from co-combustion of coal and biomass in a circulating fluidized bed combustor (CFBC). Air feeding was divided in 2 patterns, consisting of single-air staged combustion and multi-air staged combustion. The effects of position of secondary air injection, primary air and secondary air ratios and type of fuel on NOx emissions were also investigated. Coal and coconut shell were used as fuel for this research. Mixed fuel of 50% coal and 50% coconut shell was used in co-combustion experiments. Fuel feed rate and air were kept constant at 7 kg/hr and 100% air for complete combustion. The results showed that coal combustion temperature was higher than co-combustion due to the heating value of coal. NOx generated from coal combustion was higher than co-combustion because N-containing in coconut shell is less than in coal. The position of secondary air feeding at 2.4 meter 40% of total air gave the minimum NOx emissions in both cases of coal and co-combustion. In addition, multi-staged combustion was found to be an effective way to help reduce NOx from fuel combustion in CFBC.